Mode of administration influences plasma levels of active Centella asiatica compounds in 5xFAD mice while markers of neuroinflammation remain unaltered - Speers, Alex B.; Wright, Kirsten M.; Brandes, Mikah S.; Kedjejian, Nareg; Matthews, Donald G.; Caruso, Maya; Harris, Christopher J.; Koike, Seiji; Nguyen, Thuan; Quinn, Joseph F.; Soumyanath, Amala; Gray, Nora E. (Frontiers in Neuroscience, 2024)
A water extract of Centella asiatica (L.) Urban [Apiaceae] (CAW) has demonstrated cognitive-enhancing effects in mouse models of Alzheimer's disease and aging, the magnitude of which is influenced by whether CAW is delivered in the drinking water or the diet. These cognitive benefits are accompanied by improvements in oxidative stress and mitochondrial function in the brain, two pathways related to the neuroinflammatory response. The effect of CAW on neuroinflammation, however, has not been directly studied. Here, we investigated the effect of CAW on neuroinflammation in 5xFAD mice and compared plasma levels of CAW's active compounds following two modes of CAW administration. Eight-to-nine-month-old male and female 5xFAD mice and their wild-type littermates were administered CAW in their diet or drinking water (0 or 1000 mg/kg/day) for five weeks. Immunohistochemistry was performed for β-amyloid (Aβ), glial fibrillary acidic (GFAP), and Griffonia simplicifolia lectin I (GSL I) in the cortex and hippocampus. Gene expression of inflammatory mediators (IL-6, TNFα, IL-1β, TREM2, AIF1, CX3CR1, CX3CL1, CD36, C3AR1, RAGE, CCR6, CD3E) was measured in the deep grey matter. CAW decreased cortical Aβ plaque burden in female 5xFAD mice administered CAW in the drinking water but had no effect on Aβ plaques in other treatment groups. CAW did not impact elevated levels of GFAP or GSL I in 5xFAD mice, regardless of sex, brain region, or mode of CAW administration. In the deep grey matter, CAW increased C3AR1 expression in 5xFAD females administered CAW in the drinking water and decreased IL-1β expression in 5xFAD males administered CAW in the diet. CAW had no effect, however, on gene expression levels of any other inflammatory mediator in the deep grey, for either sex or mode of CAW administration. Mice administered CAW in the drinking water versus the diet had significantly higher plasma levels of CAW compounds. However, regardless of mode of administration, sex, or brain region, CAW had little impact on the neuroinflammatory markers selected for evaluation in the present study, suggesting that the cognitive benefits of CAW may not be mediated by an anti-inflammatory effect.